Carbon nanotubes, nanorings, and nanospheres: Synthesis and fabrication via chemical vapor deposition—a review - Sivamaran, V; Balasubramanian, V; Gopalakrishnan, M; Viswabaskaran, V; Gourav Rao, A; Selvamani, ST (Nanomaterials and nanotechnology, 2022)
Research work published since 2010 on the synthesis of carbon nanotubes (CNTs), carbon nanorings (CNRs), and carbon nanospheres (CNSs) using the chemical vapor deposition (CVD) process is reviewed. The effect of CVD process parameters on carbon nanomaterials morphology, such as diameter, yield, and quality was reviewed. The mechanism of CVD formation and growth of carbon nanomaterials was reviewed in detail. The catalyst materials used to synthesize these carbon allotropies were discussed in detail. The formation mechanism of carbon nanomaterials indicates that the variables of the CVD process parameters that appear to control growth are not directly manipulated in the CVD process. Rather, it is determined by complex interactions between variables. The impact of CNTs, CNRs, and CNSs was discussed using the schematic representation. The researchers who published the articles in the CNTs, CNRs, and CNSs for the past decade were discussed. From the intensive literature review, it was found that as compared to CNTs there is not much research was undertaken in synthesizing spheres and rings. But spheres and rings are capable of performing better than CNTs structure in energy storage, and sensors.